2017
DOI: 10.1089/apc.2016.0197
|View full text |Cite
|
Sign up to set email alerts
|

Retention in HIV Care and Viral Suppression: Individual- and Neighborhood-Level Predictors of Racial/Ethnic Differences, Florida, 2015

Abstract: The objective of this study was to estimate racial/ethnic differences in retention in HIV care and viral suppression and to identify related individual and neighborhood determinants. Florida HIV surveillance records of cases aged ≥13 years diagnosed during the years 2000-2014 were analyzed. Retention in care was defined as evidence of ≥2 or more laboratory tests, receipts of prescription, or clinical visits at least 3 months apart during 2015. Viral load suppression was defined as a viral load of <200 copies/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 37 publications
3
44
2
Order By: Relevance
“…Our finding is inconsistent with one study of New York City surveillance data which suggested that while neighborhood poverty was not associated with achieving viral suppression, it was associated with lower likelihood of maintaining viral suppression after diagnosis [33]. However, the literature on the effect of neighborhoods on viral suppression is mixed with some studies showing an association between residing in areas of high deprivation and poor viral suppression [34,35], and others showing no association [36,37]. It is possible that neighborhood units smaller than the ZIP code or other neighborhood characteristics not measured in this study, particularly perceptions of one's neighborhood, may be important.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our finding is inconsistent with one study of New York City surveillance data which suggested that while neighborhood poverty was not associated with achieving viral suppression, it was associated with lower likelihood of maintaining viral suppression after diagnosis [33]. However, the literature on the effect of neighborhoods on viral suppression is mixed with some studies showing an association between residing in areas of high deprivation and poor viral suppression [34,35], and others showing no association [36,37]. It is possible that neighborhood units smaller than the ZIP code or other neighborhood characteristics not measured in this study, particularly perceptions of one's neighborhood, may be important.…”
Section: Discussioncontrasting
confidence: 99%
“…Characteristics of men who have sex with men by sustained viral load suppression, 2017 (n = 3386) Characteristics of men who have sex with men by sustained viral load suppression, 2017 (n = 3386) (Continued)In the multivariate analyses the odds of sustained viral suppression were lower for younger MSM (18-24 [aOR 0.51, 95% CI 0.34-0.77] and 25-34 [aOR 0.68, 95% CI 0.52-0.87] compared with[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] year-olds) and for Black MSM compared with White MSM (aOR 0.44, 95% CI 0.29-0.69) (Table 2). Individuals not enrolled in the ACA (aOR 0.66, 95% CI 0.48-0.90), currently reporting Characteristics of men who have sex with men by sustained viral load suppression, 2017 (n = 3386) (Continued)…”
mentioning
confidence: 99%
“…The investigators chose to exclude Spanish-speaking participants from this study because care engagement in Spanishspeaking people living with HIV, who are more likely to be recent immigrants, has been shown to differ from Englishspeaking Latinos. 25 A separate interview guide would be necessary to address topics of patient/provider language barriers, the role of documentation status, care engagement, and culture/acculturation, and a separate recruitment strategy would be needed to sample this subpopulation (<10% of the overall clinics' clients), which was beyond the scope of this analysis. 26,27 From each site, 10 patient participants were interviewed who missed their IMV following their case management intake visit, defined as no-show for the IMV without cancelation by patient or provider (Missed).…”
Section: Patient Participant Inclusion and Sampling Designmentioning
confidence: 99%
“… 8 Racial and ethnic disparities remain an issue in HIV care in the United States, where black and Latino patients have lower rates of retention in care and viral suppression than white patients. 9 Discontinuity of care is higher for male than female patients and higher for black than non-black patients. 10 Nonwhite race is a risk factor for poor ART adherence, in addition to psychosocial factors of self-efficacy, depression, stigma, and stressful life events.…”
Section: Introductionmentioning
confidence: 99%